A novel mixed sustainability-resilience framework for evaluating hospital information systems. (October 2018) - Motevali Haghighi, S.; Torabi, S. Ali
Highlights: Introducing a novel comprehensive sustainability-resilience framework for HISs. Suggesting strategic actions for enhancement of HIS from a mixed sustainability-resilience framework using SWOT analysis. Using a combination of qualitative and quantitative modeling methods to evaluate a real HIS. Abstract: Information systems (ISs) are one of the most widely used systems in different organizations especially hospitals. Improving the performance of a hospital information system (HIS) is one of the most important tasks for patient satisfaction and health. To do this, a mixed sustainability-resilience framework for evaluating HISs is proposed in this study in order to enhance their performance from a mixed sustainability-resilience view. First, a comprehensive framework including suitable sustainable and resilience indicators for performance enhancement of HISs is provided. Then, the importance weight of each indicator is achieved by using the best-worst method (BWM). Required data is obtained through a standard questionnaire. A data envelopment analysis (DEA) is applied to evaluate HIS performance in different departments of a real case study. Additionally, improvement actions are obtained by considering the effect of each selected indicator on the HIS performance through a sensitivity analysis. Also, appropriate strategies for improving the resilience and sustainability aspects of the HIS are presented using strengths-weaknesses-opportunities-threats (SWOT) matrix. Using the results, designers can build more intelligent HISs from both sustainability and resilience perspectives.